Preoperative diagnosis of cavernous hemangioma presenting with melena using wireless capsule endoscopy of the small intestine - Akazawa, Yu; Hiramatsu, Katsushi; Nosaka, Takuto; Saito, Yasushi; Ozaki, Yoshihiko; Takahashi, Kazuto; Naito, Tatsushi; Ofuji, Kazuya; Matsuda, Hidetaka; Ohtani, Masahiro; Nemoto, Tomoyuki; Suto, Hiroyuki; Yamaguchi, Akio; Imamura, Yoshiaki; Nakamoto, Yasunari (Endoscopy International Open, 2016)
Background and study aims: Primary neoplasms of the small intestine are relatively rare in all age groups, accounting for about 5 % of all gastrointestinal tumors 1. Cavernous hemangiomas of the small intestine are also rare, can cause gastrointestinal bleeding, and are extremely difficult to diagnose preoperatively 2. We present a patient who presented with melena and iron deficiency anemia, for whom wireless capsule endoscopy and single-balloon enteroscopy facilitated the diagnosis of cavernous hemangioma.